Inflammatory conditions induce IRES-dependent translation of cyp24a1. - Daniela Rübsamen (PLoS ONE, 2014)
Rapid alterations in protein expression are commonly regulated by adjusting translation. In addition to cap-dependent translation, which is e.g. induced by pro-proliferative signaling via the mammalian target of rapamycin (mTOR)-kinase, alternative modes of translation, such as internal ribosome entry site (IRES)-dependent translation, are often enhanced under stress conditions, even if cap-dependent translation is attenuated. Common stress stimuli comprise nutrient deprivation, hypoxia, but also inflammatory signals supplied by infiltrating immune cells. Yet, the impact of inflammatory microenvironments on translation in tumor cells still remains largely elusive. In the present study, we aimed at identifying translationally deregulated targets in tumor cells under inflammatory conditions. Using polysome profiling and microarray analysis, we identified cyp24a1 (1,25-dihydroxyvitamin D3 24-hydroxylase) to be translationally upregulated in breast tumor cells co-cultured with conditioned medium of activated monocyte-derived macrophages (CM). Using bicistronic reporter assays, we identified and validated an IRES within the 5' untranslated region (5'UTR) of cyp24a1, which enhances translation of cyp24a1 upon CM treatment. Furthermore, IRES-dependent translation of cyp24a1 by CM was sensitive to phosphatidyl-inositol-3-kinase (PI3K) inhibition, while constitutive activation of Akt sufficed to induce its IRES activity. Our data provide evidence that cyp24a1 expression is translationally regulated via an IRES element, which is responsive to an inflammatory environment. Considering the negative feedback impact of cyp24a1 on the vitamin D responses, the identification of a novel, translational mechanism of cyp24a1 regulation might open new possibilities to overcome the current limitations of vitamin D as tumor therapeutic option.